Ethnomatematika Pada Bentuk Bangunan Rumah Marga Tjhia Di Singkawang - serly serly; Jamilah Jamilah; Dwi Oktaviana; Yadi Ardiawan (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
Abstract This research is a study of mathematics related to ethnomathematics at the house of the Tjhia clan in Singkawang. This study aims to find the mathematical concepts contained in the form of the house building so that it can be used for learning mathematics. This type of research is descriptive qualitative research. In this study, the instruments used were interview and documentation guidelines. This study will examine more deeply the history of the Tjhia Marga House and the mathematical aspects contained in the house. The mathematical concepts found in the house are the concepts of congruence and similarity, the area of ​​the flat wake, the shape of the space, the type of line and its position. Keywords: Ethnomathematics, Rumah Marga Tjhia Singkawang, mathematical aspects, traditional houses.